2009
DOI: 10.1007/s00467-009-1135-8
|View full text |Cite
|
Sign up to set email alerts
|

Membranoproliferative glomerulonephritis associated with a mutation in Wilms’ tumour suppressor gene 1

Abstract: Wilms' tumour suppressor gene 1 (WT1) encodes a transcription factor required for normal development of the genitourinary system. In the kidney, mutations in WT1 can cause diffuse mesangial sclerosis or focal segmental glomerulosclerosis. Here, we report on a girl with a mutation in WT1, who developed membranoproliferative glomerulonephritis (MPGN) 3 years after completion of treatment for Wilms' tumour. This finding extends the spectrum of glomerular disease seen with WT1 mutations and could have implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Mutations in the WT1 gene in patients with SRNS seem to be restricted to exons 8 and 9 [7]. WT1 mutations in patients with SRNS are associated with FSGS, diffuse mesangial sclerosis (DMS) or membranoproliferative glomerulonephritis [2] on biopsy. Interestingly, the same WT1 mutation (1228 +5 G>A) may be associated with different phenotypes and glomerular diseases in the same family, as shown by Denamur et al who found transmission of this mutation from a phenotypically normal (karyotype XX) mother with proteinuria and FSGS to a child with the Denys-Drash syndrome (karyotype XY) and DMS [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the WT1 gene in patients with SRNS seem to be restricted to exons 8 and 9 [7]. WT1 mutations in patients with SRNS are associated with FSGS, diffuse mesangial sclerosis (DMS) or membranoproliferative glomerulonephritis [2] on biopsy. Interestingly, the same WT1 mutation (1228 +5 G>A) may be associated with different phenotypes and glomerular diseases in the same family, as shown by Denamur et al who found transmission of this mutation from a phenotypically normal (karyotype XX) mother with proteinuria and FSGS to a child with the Denys-Drash syndrome (karyotype XY) and DMS [18].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the WT1 gene result in the occurrence of diffuse mesangial sclerosis (DMS), focal segmental glomerulosclerosis (FSGS), or membranoproliferative glomerulonephritis [2], which may appear isolated or in combination with other features, such as in the Denys-Drash and Frasier syndromes [1]. WT1 mutations have been found in a small percentage of children with isolated or syndromal steroid-resistant nephrotic syndrome (SRNS) [3][4][5], but have not been described in patients with steroid-sensitive nephrotic syndrome (SSNS) [6].…”
Section: Introductionmentioning
confidence: 99%
“…The WT1 mutation c.1372C>T (p.Arg458*) found in our patient results in truncation of the protein. This mutation has already been described as disease causing by others [5,6,8,9,10] and arginine at this position is highly conserved in evolution, which makes the pathogenicity of the mutation very likely.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a female patient with DDS was reported to have membranoproliferative glomerulonephritis type 1 (MPGN) in the native kidneys [4]. She underwent successful renal transplantation without evidence of recurrence of MPGN up to 4 years after transplantation.…”
Section: Introductionmentioning
confidence: 99%